Digital pulse width modulation sampling effect embodied steady‐state time‐domain modeling of a boost converter driven permanent magnet DC brushed motor. (1st June 2021) - Mishra, Pratikanta; Banerjee, Atanu; Ghosh, Mousam; Baladhandautham, Chitti Babu
Summary: DC‐DC converters are conventionally utilized to drive DC motors, where boost converters are employed in several emerging drive‐based applications. The modern boost converter motor drives are controlled with digital circuits due to its flexibility and cost‐effectiveness. However, the impact of the sampling in digital controllers is generally neglected during the modeling of the drives. In this paper, the sampling effect of digital controllers is analyzed for the steady‐state speed of the boost converter fed brushed permanent magnet DC (PMDC) motor drive, and the corresponding mathematical model is proposed. A relationship is established between time delay, multisampling factor, and duty ratio, which is further implemented on the PMDC motor model. The modeling shows that a time delay in pulse generation is induced due to the sampling that changes the duty ratio and the resultant motor speed. The variation in motor speed obtained from the analysis justifies the relevance of the proposed model. The proposed mathematical model shows that a high sampling frequency of the digital controller is essential to adapt the analog controller‐based motor drive behavior. However, an optimization methodology between the controller frequency and drive performance for low‐cost applications has been mentioned in this paper. The experimental analysis performed on the simulation environment and the real‐time laboratory prototype complements the precision of the proposed model. Abstract : A time delay is observed in gate pulse generation due to the sampling effect of digital controllers. Hence, the actual duty ratio differs from the ideal duty ratio, which is further prominent for low sampling frequencies. The impact of the distorted gate pulses is analyzed for the steady‐state speed of the boost converter‐fed brushed permanent magnet DC motor drive, and the corresponding mathematical model is proposed in this paper.